PENGARUH NON-CEO FAMILY OWNERSHIP DAN UKURAN PERUSAHAAN TERHADAP KONSERVATISME AKUNTANSI DENGAN FOUNDER OWNERSHIP SEBAGAI VARIABEL PEMODERASI - Mochamad Ibnu Harris; Darsono Darsono (Diponegoro Journal of Accounting, 2015)
This study aims to examine empiracally: (1) relation between non-CEO family ownership and accounting conservatism, (2) relation between company size and accounting conservatism, (3)founder ownership influence in term of relation between non-CEO family ownership and accounting conservatism.This study used a purposive sampling method in the selection of the sample, the criteria ofsamples is a manufacturing company that has managerial ownership and public ownership and then listed on the Indonesia Stock Exchange (IDX) during the period 2012-2013.The Results of this research showed non-CEO family ownershipsignificantly contribute to the selection of accounting conservatism in the financial statements, beside thatcompany size were not significantly contribute to selection of accounting conservatism. However founder ownership wassignificantly contribute in terms of non-CEO family ownership and accounting conservatism relation.